Study of Ambivalent Sexism in the Student Body of the Costa Rican Institute of Technology - Calderón Ferrey, Martha (2024)
The results of a study on ambivalent sexism and its two components, hostile sexism (HS) and benevolent sexism (BS), in students at the Costa Rican Institute of Technology (ITCR, for its acronym in Spanish) are presented. The traditional conception of sexism has been overcome by the contributions of Glick and Fiske (1996), who state that sexism is made up of the two components mentioned above, which are clearly differentiated. The first coincides with the traditional conception of sexism, and the second is a more subtle expression, which even involves a “positive” connotation based on stereotypes and traditional roles for women. Benevolent sexism implies a threat, as it can be used to mitigate or legitimize hostile sexism. This is descriptive quantitative research, which studies the variable by sex, age, or area of origin through the application of the Ambivalent Sexism Inventory (ASI), created and validated by Glick and Fiske (1996), in the Spanish version of Expósito, Moya, and Glick (1998). The sample consists of 517 students in the year 2022 (42.6% female). Student’s t-test and Kruskall-Wallis statistical techniques were used in the data analysis. As a result, it is inferred that there are low levels of ambivalent sexism, hostile sexism, and benevolent sexism: there are differences between men and women in hostile and benevolent sexism, the first ones presenting higher levels, with high effect sizes in both cases. The results can be interpreted as positive, considering the low level of sexism observed in all three categories. However, given the high educational level of this population, it was expected that there would not be high levels of sexism, since research by Glick, Lameiras-Fernández, and Rodríguez Castro (2002) and León and Aizpurúa (2020) found that the higher the level of education, the lower the levels of sexism, and because the ITCR has a strong history of incorporating provisions, both in its general and specific policies as well as in its academic model, that place the human being as the most important thing. The findings suggest that the efforts made have not been sufficient; therefore, it is necessary to continue and strengthen actions aimed at eliminating both conceptions and sexist behavior among students.